Insights into the expectations of mobility students: the impact of Erasmus in their future professional careers - Pinheiro, Margarida M. (2020)
At the celebration of its 30th anniversary, Erasmus is recognised as the most successful exchange program ever implemented. The prospects of attaining a common European consciousness challenged the program's ability to blend together knowledge, attitudes and skills in a winning combination. It is no longer sufficient to communicate and integrate: mobility should actively foster skills to support students's professional career at national and international levels. Although literature on mobility is vast and interesting, studies on the impact of the mobility experience in the students' future employability profile rarely provide first-hand data on their expectations in this regard. This exploratory research comprises a qualitative focus group approach with Erasmus students during their exchange period in a Portuguese university and collected some insightful data on how students consider their mobility in terms of new learning outcomes, the professional value of the experience and the development of new skills. Results indicate that students seem to be quite aware of the positive implications of mobility in their professional careers and of the set of skills developed during that period. Overall, this article contributes to demonstrating the importance of assessing skills development during Erasmus mobility experiences. Managerial implications and suggestions for future research are provided.